State and Civil Society: Peculiarities of the German Approach - Ekaterina P. Timoshenkova (Современная Европа)
The article is dedicated to the interaction between the German state and civil society (CS). Germany is known as a developed democratic state with a strong CS in which non-governmental organizations play an active role. They also help the German government to implement its foreign policy vision and maintain its image abroad. The article addresses the question whether German NGOs are equal partners of the state and to what extent they are independent in reality. The author analyses the legal status and financing features of German NGOs, examines the concepts of interaction between the state and CSOs and highlights their underlying principles. The study makes a clear distinction between the academic approach and the state/government approach. For this purpose, the author examines theoretical papers by German academics and analyses conducted by the Bundestag, especially the "Ethics Commissions" of 2002, and compares the German approach to NGOs with other international practices. The article reveals the main points of interaction between the state and CSOs during the chancellorship of G. Schroeder and A. Merkel. The red-green coalition model is analyzed in more detail, as it has become the basis of the modern "social contract". The author concludes that there is no civil society in the classical scientific sense in the FRG. The German state not only actively supports its NGOs financially, but also defines the rules of engagement by clearly identifying organizations that seek political influence.